From Which Direction Does the Empire Strike (Back)? - Halicki, Katharina Theresa; Ingendahl, Moritz; Mayer, Maren; John, Melvin; Schreiner, Marcel Raphael; Wänke, Michaela (Frontiers in Psychology, 2021)
AIn cultures with left-right-script, agentic behavior is mentally represented as following a left-to-right trajectory, an effect referred to as the Spatial Agency Bias (SAB, Suitner & Maass, 2016). In this research, we investigated whether spatial representations of activities are universal across activities by analyzing the opposite concepts of “attack” and “defense”. Both behaviors involve similar actions (e.g. fighting) but may differ in perceived agency. Moreover “defense” is necessarily always a response to an attack and may therefore be represented by a trajectory in the opposite direction. Two studies found the classic SAB for activities representing attacking but a reduction (Study 1) and reversal (Study 2) for activities involving defense. Although the spatial representation of defense on the right was much weaker and less unequivocal than that of attack on the left, the results suggest that the spatial representations of defense and attack are located in different positions. Apparently not all actors and all activities are spatially represented on the left with a left-to-right trajectory but position and direction depend on the perceived agency. Directions for future research and applications of our findings are discussed.